Analisis Implementasi E-Faktur 3.0 Dalam Meningkatkan Kepatuhan Wajib Pajak Pada KPP Pratamabandar Lampung Dua - Astria Adetasya Putri Suendra; Diana Prihadini (Jurnal Ilmu Administrasi Publik, 2021)
In order to realize a safe, orderly, just and prosperous nation's life, it is necessary for the state to have sources of income, one of which is in the form of Value Added Tax (VAT). However, the emergence of the COVID-19 pandemic has greatly shaken the Indonesian economy. The state must increase its spending to contain the epidemic and maintain the economy. The drag on tax and state revenues has been another challenge. Therefore, on October 1, 2020, the Directorate General of Taxes (DGT) officially launched the e-faktur application version 3.0 with the aim of making it easier for taxpayers to fulfill their tax obligations which is expected to increase taxpayer compliance and increase state revenue. The purpose of this study was to analyze the implementation of e-faktur 3.0, the obstacles to implementing e-faktur 3.0, and the efforts made to overcome these obstacles in order to increase taxpayer compliance at the Primary Tax Office of Bandar Lampung Dua. Data collection methods used in this study were observation, interviews, documentation and literature study. This study used the theory of George C. Edward III which carries the variables of communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of e-faktur 3.0 has fulfilled all the variables needed to improve taxpayer compliance. Meanwhile, the inhibiting factors are the frequent occurrence of errors or maintenance in applications and counseling or campaign regarding the implementation of e- faktur 3.0 which cannot be carried out face-to-face due to the COVID-19 pandemic. The efforts of the Primary Tax Office of Bandar Lampung Dua in overcoming these obstacles are to provide a consultation or help desk and online media for taxpayers.